A Cross-Sectional Survey On An Insight Into The Current Perceptions Of Indian Radiologists, Radiographers, Radiology Trainee & Medical Imaging Students On The Future Impact Of Artificial Intelligence (AI) On The Profession (Journal of Pharmaceutical Negative Results, 2023)
Objective: This study will help in assessing the knowledge and perception of Radiologists, radiographers, trainees, and Medical imaging students about artificial intelligence.Background: An AI is a machine that has been developed to mimic human intelligence in its thinking and behavior. This term can also be applied to any machine that demonstrates cognitive abilities like learning and problem-solving. Artificial intelligence is at its best when it can evaluate alternative courses of action and select the one that offers the greatest probability of success in reaching a given objectiveMethod: A questionnaire was prepared and circulated through google Forms to Radiologists, radiographers, trainees, and Medical imaging students about artificial intelligence. A total of 268 participants took part in this research.Conclusions: In conclusion, study respondents were generally optimistic about AI. The future will depend on what we do now and shortly to take advantage of AI's many prospects for radiology, radiology residents, radiology techs, and trainees. AI will affect radiology faster than other medical areas. Residents and technologists may spearhead this shift. Radiologists' reluctance to adopt AI may be paralleled by pilots' early resistance to autopilot technology. Radiologists are acclimated to technological problems since radiology has always been a technology testing ground. Residents and technologists don't need to know the deepest aspects of these systems, but they must understand the data scientists' technical terminology to communicate effectively. Radiology needs AI immediately.